PREVALENCE AND INTENSITY OF NEMATODE PARASITES OF Poeciliareticulata PETERS (1859) IN FOUR WASTEWATER DRAINS OF LAGOS STATE, NIGERIA (2013)
Poeciliareticulata (guppy) a common ornamental tropical fish is found in many wastewater drains in Nigeria. Guppies feed on copepods which are intermediate hosts of some nematode parasites of culturable fish species. The restriction on the importation of ornamental fishes into Nigeria has enhanced the demand for local species, usually sourced from the wild. There is dearth of information on the parasites of ornamental fishes in Nigeria. This study was aimed at determining prevalence and mean intensity of the nematode parasites of P.reticulata from four waste water drains in Lagos State. Sampling was carried out monthly using a 2 mm mesh-sized scoop net along selected drains at Igi-Olugbin Street (A), Basil Ogamba Street (B), Ahmadu Bello Road (C) and AdenaikeAlagbe Street (D) between March, 2004 and February, 2005. The selected drains were contiguous to human habitation and industrial activities but each in different local government areas of Lagos State. Sixty female and sixty male samples were randomly selected from each drain for dissection and microscopy. Nematodes observed were identified using standard identification guides. Prevalence was determined as percentage infection in guppies examined. Intensity was determined as total parasite count per host. They were calculated in relation to sex of guppies and drain location for sample collection. Measurements of wastewater temperature, Dissolved Oxygen (DO), pH and transparency were done according to APHA methods. Drain depth was determined using a calibrated pole. Data was analyzed using chi-square test, ANOVA and Pearson correlation coefficient. Nematodes recovered were Eustrongylidesignotusfrom peritoneum, Camallanuscotti from duodenum and anus, Capillariapterophylli from intestine andTrichinellaspecies from muscle. Out of 4,320 fish hosts examined, E. ignotus was the most prevalent parasite (3.6 %) and Trichinellaspeciesthe least prevalent (1.5 %). Prevalence did not differ significantly with sex and drain. Mean intensities were 0.3 ± 0.3 ± 5.0 ± 1.8: males, 0.3 ± 0.3 ± 4.9 ± 1.8: females and 1.3± 1.3 - 7.0 ± 3.0: drains. Monthly mean intensity did not differ significantly with sex but differed significantly with drains (p < 0.05). Mean monthly physicochemical parameters for drains were: temperature, 25.0 ± 1.1 - 26.0 ± 1.1 o C; DO, 7.8 ± 2.1 - 8.4 ± 1.8 mg l-1; pH, 6.9 ± 0.5 - 7.3 ± 0.4; transparency, 3.5 ± 0.8 - 23.0 ± 3.6 cm and drain depth, 9.6 ± 2.3 - 14.8 ± 3.2 cm. There was no significant difference in mean monthly pH and DO across drains. However, mean monthly temperature, transparency and drain depth were significantly different across drain (p < 0.05). High correlation were observed at drain D between the prevalence of Trichinellaspeciesand wastewater DO (r2 = 0.8), between prevalence of C. pterophylli and wastewater temperature (r2 = - 0.6) and also between mean intensities of C. pterophylliand Trichinellaspecies (r2 = 0.8). Prevalence and intensity of nematodes in Poeciliareticulata was low. However, the occurrence of parasites in the guppy requires appropriate treatment of fish before introduction into culture system.